2015
DOI: 10.1016/j.medici.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A mini volume loading test for indication of preoperative dehydration in surgical patients

Abstract: Signs of dehydration were observed during mVLT in patients after pre-operative overnight fast. A revised transcapillary reflux model was proposed to explain the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Second, only 71 of 219 patients underwent echocardiographic examination, thus weakening the analysis of the echocardiographic variables. Finally, we did not attempt to identify patients pre‐operatively who might respond to fluid challenges (eg passive leg rising test or a mini‐volume loading test). Instead, we aimed for a fluid management procedure that would be simple to mimic daily practice without the risk of volume overload.…”
Section: Discussionmentioning
confidence: 99%
“…Second, only 71 of 219 patients underwent echocardiographic examination, thus weakening the analysis of the echocardiographic variables. Finally, we did not attempt to identify patients pre‐operatively who might respond to fluid challenges (eg passive leg rising test or a mini‐volume loading test). Instead, we aimed for a fluid management procedure that would be simple to mimic daily practice without the risk of volume overload.…”
Section: Discussionmentioning
confidence: 99%
“…Although the operational conditions of laparoscopic cholecystectomy includes pneumoperitoneum and the reverse Trendelenburg position and both can cause an excessive preload-dependent state, considering laparoscopic cholecystectomy is a less-invasive surgery with minimal bleeding risks, the volume for conventional fluid responsiveness test can be relatively large and may cause a volume overload postoperatively. Although the mini-volume test uses relatively small volumes, it has been used in many previous studies and showed good results [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…We retreived and retrospectively analysed data from our previous randomized controlled trial (Clinicaltrials.Gov, identifier: NCT01355900) in patients who had elective primary total knee arthroplasty (TKA) surgery [2], [7]. The adhesive spectrophotometric sensor (ReSposable R2-25a; Masimo Inc., Irvine, CA) connected to the Radical-7 Pulse CO-Oximeter (Masimo Inc.; software version 7.6.2.1) was used to measure SpHb.…”
Section: Methodsmentioning
confidence: 99%
“…An antecubital cannula for infusion was placed in the same arm. The stepwise infusion was administered according to a revised goal directed therapy (revGDT) protocol consisting of conventional GDT supplemented by the mVLT [2]. The cPDE and acPED were obtained in 48 subjects who had two mVLT sessions -before the induction of anesthesia (preoperative session) and again 24 hours later (post-operative).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation